Data Analysis for Interactive Spanish (i-Spanish) in Virtual Reality Environment: A Case Study in University Malaysia Pahang (UMP) - Siti Normaziah, Ihsan; Rahmah, Mokhtar; Chan, Quok Qeith; Noraniza, Samat; Abbas Saliimi, Lokman; Azlina, Mohd Ariffin (2015)
This paper emphasizes on data analysis towards User Acceptance Test (UAT) of i-Spanish lesson that has been developed as a learning tool to learn Spanish Language. The objective of this paper is to analyze the user acceptance of learning foreign language using interactive learning software. The testing has been done to 100 students of University Malaysia Pahang (UMP) who have taken the Spanish Language Subject. The result shows that 77% of the students accept i-Spanish as a tool for learning Spanish Language. This finding indicates that i-Spanish can potentially be one of the efficient tools in learning Spanish Language. Through the implementation of various virtual environments, the students could better understand the words they are learning, especially everyday objects. Furthermore, the courseware also allows students to learn the language at any place and anytime. The use of 3D technology will give the students the experience of real environment and will improve their capability in mastering the foreign language.